(untitled) (Revista de História da UEG (REVHIST), 2017)
Abstract: It was not Christopher Columbus who first discovered America. In fact, America was known in the Ancient Times. During the High Antiquity there was talk of an “awful country” located in the “far west”; a country that “ended” the “infertile and dark sea”. At the time of the Pax Romana, moreover, Strabo, the illustrious geographer, was emphatic: Ulysses’ adventures happened in the Atlantic Ocean. As a result, the opinion that “Scheria”, land of the Phaeacians, was the island of Corfu, in Greece, should be rejected. For Scheria, “isolated from the rest of humanity”, should be in the Iberian Peninsula. Once more Strabo was categorical: a town therein was named after Ulysses, the king of Ithaca. Finally yet importantly, according to the tradition the very etymon of Lisbon is Ulixes[1]. Keywords: Ulysses. Atlantic Ocean. Americas. Bermuda. Lisbon. [1] I would like thank Professor Eduardo Henrique Barbosa de Vasconcelos, from Universidade Estadual de Goiás, for his invitation to write this article and review it.